2021
DOI: 10.1128/aem.02707-20
|View full text |Cite
|
Sign up to set email alerts
|

New Endohyphal Relationships between Mucoromycota and Burkholderiaceae Representatives

Abstract: Mucoromycota representatives are known to harbour two types of endohyphal bacteria (EHB) – Burkholderia related endobacteria (BRE) and Mycoplasma related endobacteria (MRE). While both BRE and MRE occur in fungi representing all subphyla of Mucoromycota, their distribution is not well studied. Therefore, it is difficult to resolve the evolutionary history of these associations in favour of one of the two alternative hypotheses explaining their origin: “early invasion” and “late invasion”. Our main goal was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…If endohyphal associations have an ancient origin, the ability to form associations with bacteria could be a common synapomorphic trait in the Mortierellaceae lineage. We detected at least four bacterial species, which, based on their taxonomic placement, are possibly endohyphal (Ohshima et al, 2016;Uehling et al, 2019;Okrasiñska et al, 2021). Mycoavidus cysteinexigens was the most frequently detected one.…”
Section: Mortierellaceae Is Associated To Different Bacteriamentioning
confidence: 89%
“…If endohyphal associations have an ancient origin, the ability to form associations with bacteria could be a common synapomorphic trait in the Mortierellaceae lineage. We detected at least four bacterial species, which, based on their taxonomic placement, are possibly endohyphal (Ohshima et al, 2016;Uehling et al, 2019;Okrasiñska et al, 2021). Mycoavidus cysteinexigens was the most frequently detected one.…”
Section: Mortierellaceae Is Associated To Different Bacteriamentioning
confidence: 89%
“…Soilborne fungi of Mortierella spp. harbor Burkholderiaceae -related endobacteria (BRE) ( 1 7 ) that can protect the host from nematode attack and inhibit zygospore formation ( 8 , 9 ). Entomortierella parvispora E1425 (JCM 39028, synonymously known as Mortierella parvispora E1425) isolated from forest soil possesses a cultivable BRE named Mycoavidus sp.…”
Section: Announcementmentioning
confidence: 99%
“…Recent studies have demonstrated Mortierellaceae can harbor endobacterial symbionts [ 19 22 ]. However, the impacts of endohyphal bacteria on the PGP phenotype have not been assessed.…”
Section: Introductionmentioning
confidence: 99%